The effect of activated carbon on the adsorption of coconut shell liquid smoke on the coagulation process of latex clone PB 260 - Feerzet Achmad; Deviany Deviany; Asyifa Duwiyan Nuril Huda; Hottua Ernest Fortunatus; Arysca Wisnu Satria; Reni Yuniarti; Wika Atro Aryani; Ummul Habibah Hasyim (Konversi, 2026)
This study investigated the effectiveness of coconut shell–derived liquid smoke (CLS) and activated carbon–treated liquid smoke (CLSC) as natural coagulants for natural rubber latex clone PB 260, compared with 2% formic acid (FA). Rubber quality was assessed based on Total Solid Content (TSC), Dry Rubber Content (DRC), initial plasticity (Po), Plasticity Retention Index (PRI), ash content, dirt content, volatile matter, and Mooney viscosity according to the SNI 06-1903-2017 standard for Indonesian Standard Rubber (SIR 20). Experiments were conducted using fresh latex from clone PB 260 under the D3 tapping system, with 150 mL of latex treated with each coagulant. FA produced the fastest coagulation time (3.39 min), while CLS and CLSC required 4.37 and 4.29 min, respectively. CLS showed the highest DRC (15.33%), whereas CLSC provided better rubber stability with the highest PRI (85.83%) and high Mooney viscosity. All coagulants met SIR 20 limits for ash, dirt, and volatile matter, although Po values remained below the standard.